Islamic Zanzibar Between the Indian Ocean and the African Mainland - Nieber, Hanna (2019)
Through a discourse on religious difference, Zanzibar's belonging to both the Indian Ocean and the Tanzanian mainland is enacted and challenged. While Zanzibar is often described as a space of encounter forming a cosmopolitan society, I argue in this contribution for attention to moments of differentiation that these encounters evoke.